New micelle myricetin formulation for ocular delivery: improved stability, solubility, and ocular anti-inflammatory treatment. (1st January 2019) - Sun, Fengyuan; Zheng, Zhou; Lan, Jie; Li, Xuefei; Li, Mengshuang; Song, Kaichao; Wu, Xianggen
Abstract: Myricetin (Myr) is a naturally occurring flavonoid exhibiting diverse biological and pharmacological properties, but its characteristics such as water insolubility, poor aqueous stability, and poor bioavailability limit its clinical application, including in ophthalmology. To increase its clinical application in ophthalmology, Myr was designed to be encapsulated in a polyvinyl caprolactam–polyvinyl acetate–polyethylene glycol graft copolymer (PVCL-PVA-PEG) polymeric micelles to increases its aqueous solubility, stability, and corneal permeability to promote its efficacy in eye disease treatments. Thus, the Myr micelle ophthalmic solution was prepared and characterized encapsulation efficiency (EE), micelle size, and zeta potential. The chemical stability of Myr and the short-term storage stability of the Myr micelle ophthalmic solution were evaluated, followed by in vitro cytotoxicity and in vivo ocular irritation; in vitro cellular uptake and in vivo corneal permeation; and in vitro antioxidant activity and in vivo anti-inflammatory efficacy were also further evaluated. Myr could be incorporated into micelles with high EE. PVCL-PVA-PEG micelles significantly enhanced Myr's aqueous solubility and chemical stability. The Myr micelle ophthalmic solution also showed high storage stability. In rabbits, the Myr micelle ophthalmic solution displayed good in vitro cellular tolerance. Remarkable improvements in in vitro cellular uptake and in vivo corneal permeation were also observed in the Myr micelle ophthalmic solution, and significant improvements in the in vitro antioxidant activity and in vivo anti-inflammatory efficacy were also obtained. Overall, these results supported that the Myr micelle ophthalmic solution could be a promising nanomedicine for ocular tissues.